ANALISIS FILSAFAT HUKUM ATAS GERAKAN PEMBANGKANGAN SIPIL DALAM KONTEKS MASYARAKAT DEMOKRASI MODERN - Muthmainnah, Lailiy (Undiksha, 2023)
Compliance with the law is generally understood as a necessity so that violation of the law means punishment. In contrast to the usual type of law violation, civil disobedience is often chosen by citizens as a means to voice the aspirations of the community when formally existing channels are deemed unable to work anymore. In the context of modern democratic society, this is interesting to study considering that citizens' obedience to the law is essential and is a logical consequence of the justification of the state through the mechanism of social contracts. Therefore, the civil disobedience movement will raise problems in the context of state legitimacy. This is the focus of the study in this research. The method used in this research is philosophical hermeneutics with methodical elements of interpretation, coherence, holistic, idealization, heuristics, and description. The results of the study indicate that the civil disobedience movement is an attempt by citizens to pressure the government to review moral standards which will later be applied to society through legal mechanisms. In this context, the emphasis is that the law should not only be seen as a formal rule (quid iuris) that must be obeyed by all citizens, but the law must reflect social justice (quid ius). When substantively the existing legal rules are believed to have violated the principles of community justice, civil disobedience is better understood as a moral obligation, not just a right, so that the consequences of punishment can be ignored. The spirit of resistance brought by the civil disobedience movement will always be anchored in the moral awareness of the function of justice in law. Civil disobedience becomes the moral face of lawlessness that has radical transformative power to reshuffle existing institutions or socio-political order. This is an inevitability in the constitutional democratic process that continues to undergo change, refinement, and never final.